FAMILY LYGISTORRHINIDAE - Oliveira, Sarah Siqueira; Amorim, Dalton De Souza (Zootaxa, 2016)
The Lygistorrhinidae are a family belonging to the suborder Bibionomorpha, with no previous record from Colombia. This paper refers for the first time to the occurrence of the family in the country, an undetermined species of the genus Lygistorrhina (Probolaeus) Williston.